FAKTOR YANG BERPERAN DAN DINAMIKA PSIKOLOGIS YANG TERJADI PADA MAHASISWA SAAT MELAKUKAN KECURANGAN AKADEMIK - Anna Armeini (Perspektif Ilmu Pendidikan, 2011)
Academic misconduct performed by the university students is an illegal practise and will give negative effects to the individual as well as the related institution. This research aims at discovering significant factors and psychological dynamics in the university students performing academic misconduct. The research based on the post positivistic paradigm with three students of State University of Jakarta as the objects of the study. Using interview technique in collecting data, the research conducted in the odd semester of 2009/2010 concludes that demographic factor, individual factor, and situational factor are the signifant factors. The academic misconduct performer has a psychological dynamic showing dissonance. The performer believes academic misconduct is inapprorate, but he/ she still keeps doing.